FOAM GLASS GRAVEL MADE OF RECYCLED GLASS WASTE AND SILICON CARBIDE BY MICROWAVE HEATING - LUCIAN PAUNESCU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2020)
The paper presents recent achievements in the microwave use for manufacturing foam glass gravel from recycled glass waste and silicon carbide. The aim was to obtain a product with physical and mechanical characteristics almost similar to those of industrially manufactured materials by conventional heating techniques, but with a higher energy efficiency. A foam glass with the thermal conductivity of 0.075 W/m·K and the compressive strength of 7.5 MPa was experimentally obtained. The specific energy consumption was of 1.0 kWh/kg comparable with the industrial processes and it could reach values up to 25% lower by using a high power industrial microwave equipment.